임상치과위생사의 임파워먼트에 관한 연구 - 신선행; Shin, Seon-haeng (Chiwisaeng gwahakoeji, 2010)
This study was conducted to collect the basic data to provide for the purpose of the development of dental field. This research is to find the relationship between the level of recognized empowerment of hygienists working in dental clinics and the factors influencing on work achievement in the system of dental clinics. The population of the research is some randomely chosen dental clinics located in Seoul City during the period from March 22 to April 30, 2010, and the sample of 256 female dental hygienists working in the field were recruited as the analysis object group. The data on general characteristics and empowerment were collected by a questionnaire survey. The collected data were analyzed with the SPSS WIN 12.0 program. The following shows the results of this study. 1. The empowerment level of the analysis subject group was 3.63. It is significant statistically that the longer working career or higher annual salary, the higher empowerment level (p<0.05). 2. It shows the high level of empowerment in the group of hygienists who are in education counsel (p<0.01), and who have a permanent job (p<0.05) than others. 3. There is a significant correlation among capability, age, career, annual salary (p<0.01). 4. There is a significant correlation among self determination, age(p<0.05), career (p<0.01), annual salary (p<0.05). 5. In regression analysis, career is proved as one of the significant factors that is related to the empowerment in dental hygienists (p<0.05). This finding shows high level of empowerment in dental hygienists who hold high level of career, annual salary, education counsel jobs, or permanent jobs. Therefore, I suggest with the result of the study that the organization of dental clinic needs to improve its capability and efficiency with the efficient manpower management. Particularly, there need to be various kinds of leadership-trainning and education-program development to enhance empowerment in hygienists as professionals through independent self-decision making experiences and role do experiences. 치과위생사가 지각하고 있는 임파워먼트 정도와 병원조직 내에서 업무성과에 영향을 미치는 요인들간의 관계를 파악하여 치과의료 발전에 도움이 될 기초자료를 제공하고자 2010년 3월22일부터 4월 30일까지 서울에 소재하고 있는 일부 치과의료기관을 임의추출하여 재직하고 있는 여자 치과위생사 256명을 분석대상으로 하였다. 설문지를 이용하여 일반적 특성, 임파워먼트에 관한 자료를 수집하였고, 수집된 모든 자료는 SPSS 12.0 통계프로그램을 이용하여 분석하였다. 본 연구 결과는 다음과 같다. 1. 연구대상자의 임파워먼트 수준은 3.63이었고, 근무경력, 연봉이 많을수록 임파워먼트가 높아 통계적으로 유의한 차이를 보였다(p<0.05). 2. 교육 상담업무(p<0.01), 정규직(p<0.05)에서 임파워먼트가 높았다. 3. 역량성과 연령, 근무경력, 연봉은 상관관계가 있었다(p<0.01). 4. 자기결정성과 연령(p<0.05), 근무경력(p<0.01), 연봉(p<0.05)은 유의한 상관성이 있었다. 5. 회귀분석 결과, 임파워먼트와 유의한 관련성이 있는 요인은 근무경력(p<0.05)이었다. 결론적으로 직무관련 치과위생사의 임파워먼트는 근무경력, 연봉, 교육 상담업무, 정규직에서 높게 나타났다. 이로써 치과조직은 효율적인 인력관리를 통해 조직의 역량과 효과성을 높여야하며, 특히 치과위생사가 전문직으로서의 독자적인 의사결정이나 역할수행을 통해 스스로 임파워먼트를 증진시킬 수 있는 리더십 훈련과 다양한 교육프로그램 개발이 마련되어야 할 것이다.